Alkali silica reaction of BOF and BFS wastes combination in cement - Özkan, Ömer; Sarıbıyık, Mehmet (Journal of Civil Engineering and Management, 2013)
This study reports the results of an experimental study conducted to determine composite cements manufactured with the combination of Basic Oxygen Furnace (BOF) Slag and Blast Furnace Slag (BFS). The overall objective of this work is to determine whether a combination of BOF slag and BFS can be used as a cementations material to produce Composite Portland Cement (CPC). Three groups of cement are produced for testing. The first group contains BOF slag, the second group contains BFS and the last group contains the mixture of BOF slag and BFS together. Physical properties and Alkali Silica Reaction (ASR) of these groups are also evaluated in this study. Maximum ASR expansion is observed from the sample of CPC created with BOF slag. On the other hand minimum ASR expansion value is located in the sample of CPC created with BFS only.